Effects and safety of atmospheric low‐temperature plasma on bacterial reduction in chronic wounds and wound size reduction: A systematic review and meta‐analysis. Issue 1 (12th October 2018) - Assadian, Ojan; Ousey, Karen J.; Daeschlein, George; Kramer, Axel; Parker, Christina; Tanner, Judith; Leaper, David J.
Abstract : The use of atmospheric low‐temperature plasma (AP) on chronic wounds and its effect on microbial bioburden in open wounds has not been explored with a systematic review and meta‐analysis. PRISMA guidelines were followed and PubMed, Embase, CENTRAL, and CINAHL databases searched for randomised controlled trials (RCTs), which compared AP with no AP for the management of open, chronic wounds. The primary outcomes of reduction of bioburden or wound size were included. Meta‐analyses were performed; odds ratio (OR) and 95% confidence intervals (CIs) were extracted and pooled in a random effects model. Four RCTs investigated the effect of AP on chronic wound healing. Chronic wounds treated with AP did not show a significant improvement in healing (AP vs control: OR = 1.46; 95% CI = 0.89‐2.38; P  = 0.13). Five further RCTs investigated the reduction of bioburden in wounds, but AP demonstrated no significant reduction of bioburden (AP vs control: OR = 0.85; 95% CI = 0.45‐1.62; P  = 0.63). All nine RCTs recorded the presence of any severe adverse events (SAEs) in the 268 patients studied, with only one unrelated SAE identified in each group (AP vs control: OR = 1.00; 95% CI = 0.05‐19.96; P  = 1.00). Use of AP in wound care is safe, but the retrieved evidence and meta‐analysis show that there is no clinical benefit of AP in chronic open wounds using currently available AP device settings.